Climate change is beyond any one of us - The work of public health practitioners in building resilience against climate effects (BRACE) programs - Zechariah J. Lange; Fushcia-Ann Hoover; Tisha J. Holmes; Christopher K. Uejio (Sustainable Environment)
Public health practitioners of the Center for Disease Control and Prevention’s (CDC) Climate Ready States and Cities Initiatives operate through critical pragmatism, programmatic facilitation, and collaborative planning to address climate and health impacts at the local and state levels. The study utilized qualitative mixed methods of semi-structured interviews and climate and health adaptation plan analysis to investigate the CDC’s 2010–2021 funded cohort of 18 programs across the United States. The research presented here is an exploration of how these care-driven practitioners are constructing networks across scales, agencies, and the public(s) to construct, implement, and evaluate planning strategies in the face of severe barriers and challenges. Practitioners are investing in relational methodologies capable of generating targeted and reflexive programming, which is in line with progressive planning practices. Moreover, practitioners are utilizing these relational methodologies in a manner akin to ‘context-responsiveness’ to cross institutional and structural boundaries as well as generate and utilize limited resources. Finally, the research concludes by presenting a case for greater inter- and transdisciplinary practices across professional fields and universities to confront and mitigate the severe and growing health impacts of climate change.